2021
DOI: 10.2147/ppa.s310613
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between COVID-19 Related Stress and Medication Adherence Among High-Risk Adults During the Acceleration Phase of the US Outbreak

Abstract: Purpose: To assess the relationship between stress regarding COVID-19 and medication adherence. Patients and Methods: Older adults with ≥1 chronic condition(s) were recruited from 4 active, federally funded studies in Chicago to participate in a longitudinal telephone survey. Participants self-reported stress regarding COVID-19 in the last week. Adherence was measured via the ASK-12 survey. Results: Most participants reported feeling stressed "some of the time" (54.0%), while 18.2% felt stressed "most" or "all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…The global crisis due to the coronavirus disease 2019 (COVID-19) pandemic has brought significant changes across many aspects of our society. An aspect that has not yet received due attention is the evolution in drug utilization due to COVID-19 as a consequence of the barriers in using healthcare facilities, because of changes in lifestyle, future prospects and as a result of medication management practices that most healthcare systems have implemented to reduce the impact of pandemic events ( Clement et al., 2021 ; Patel et al., 2021 ; Zhao et al., 2021 ; Agh et al., 2021 ; Kardas et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The global crisis due to the coronavirus disease 2019 (COVID-19) pandemic has brought significant changes across many aspects of our society. An aspect that has not yet received due attention is the evolution in drug utilization due to COVID-19 as a consequence of the barriers in using healthcare facilities, because of changes in lifestyle, future prospects and as a result of medication management practices that most healthcare systems have implemented to reduce the impact of pandemic events ( Clement et al., 2021 ; Patel et al., 2021 ; Zhao et al., 2021 ; Agh et al., 2021 ; Kardas et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the results we have seen during the pandemic, those who decided to accept the possible risks of being close to other people, including their orthodontists, were the ones who decided to receive orthodontic treatment. The same patients reported unchanged or increased availability of their orthodontist during the pandemic [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is expected that anxiety results in high adherence to preventive measures, although research evidence remains mixed. Whilst some studies have shown positive relationship between anxiety and adherence to preventive measure, others found no or negative association [ 97 , 98 ]. The findings of this study thus concur with others that found that increased anxiety is associated with positive preventive behaviour.…”
Section: Discussionmentioning
confidence: 99%